2006
DOI: 10.1111/j.1654-1103.2006.tb02450.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term changes of the vascular epiphyte assemblage on the palm Socratea exorrhiza in a lowland forest in Panama

Abstract: Question: What are the qualitative and quantitative long‐term changes in the vascular epiphyte assemblage on a particular host tree species? Location: Lowland rain forest of the San Lorenzo Crane Plot, Republic of Panama. Methods: We followed the fate of the vascular epiphyte assemblage on 99 individuals of the palm Socratea exorrhiza by three censuses over the course of five years. Results: The composition of the epiphyte assemblage changed little during the course of the study. While the similarity of ep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
22
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 26 publications
4
22
0
Order By: Relevance
“…Comparisons of the epiphyte vegetation on individual host trees, as well as in the entirety of host trees show that the temporal changes of the epiphyte vegetation on a single tree were low, and the epiphyte vegetation on Annona glabra as a whole became more homogeneous. A different pattern was found by Laube & Zotz (2006) in another lowland forest for the epiphyte vegetation on the palm Socratea exorrhiza. They showed that the similarity of an epiphyte vegetation on a single tree decreased considerably in time while the vegetation on all studied host trees in the area became more similar.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Comparisons of the epiphyte vegetation on individual host trees, as well as in the entirety of host trees show that the temporal changes of the epiphyte vegetation on a single tree were low, and the epiphyte vegetation on Annona glabra as a whole became more homogeneous. A different pattern was found by Laube & Zotz (2006) in another lowland forest for the epiphyte vegetation on the palm Socratea exorrhiza. They showed that the similarity of an epiphyte vegetation on a single tree decreased considerably in time while the vegetation on all studied host trees in the area became more similar.…”
Section: Discussionmentioning
confidence: 61%
“…Such a unimodal pattern may be explained by a non-equilibrium metapopulation status of the epiphyte species on Annona glabra: new colonizations of available empty patches exceed extinction events (Table 4) which is caused by the ongoing colonization of habitat patches by epiphytes due to their, in epiphyte terms, quite recent establishment of less than 80 years. Another study by Laube & Zotz (2006) already showed that a time span of this magnitude does not allow epiphytes to colonize a patch completely. In that study the average available time for epiphytes to colonize a palm tree before it died was 60 years, which turned out to be too short to colonize a patch completely given the slow growth of epiphytes (Schmidt & Zotz 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Studies of epiphyte species richness in relation to tree size usually indicate a strong positive relationship (Flores-Palacios and García-Franco 2006;Laube and Zotz 2006;Zotz and Schultz 2008). However, there are also a few observations that suggest no positive relationship (Boelter et al 2011) or even saturation of species richness with tree size (Hietz and Hietz-Seifert 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Species richness patterns of epiphytes are closely related to the morphological, architectural, and phenological characteristics of the respective host tree (Wagner et al 2015). Host tree size, in particular, has been identified as an important factor influencing species richness and individual abundances of the epiphyte community: Species richness usually increases strongly with host tree size (Flores-Palacios and García-Franco 2006;Laube and Zotz 2006). As the tree ages, its characteristics change, which affects the development of the epiphyte community (Laube and Zotz 2007;Taylor and Burns 2015;Woods et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in typical plot-based sampling designs, most of the observed epiphyte and tree species are rare (e.g. Laube & Zotz, 2006).…”
Section: Introductionmentioning
confidence: 99%